Parallel stent retriever mechanical thrombectomy of an acute internal carotid artery occlusion refractory to standard techniques: A case report - Yoshimoto, Takeshi; Hosoki, Satoshi; Tanaka, Kanta; Koge, Junpei; Satow, Tetsu; Yamagami, Hiroshi; Toyoda, Kazunori; Ihara, Masafumi (Frontiers in Stroke, 2023)
Although mechanical thrombectomy for acute large vessel occlusion is generally effective, some occlusions are refractory. We report a patient in whom the parallel stent retriever technique using two Trevo stent retrievers (Stryker Neurovascular, Fremont, California, USA) was required to treat an intracranial and epidural internal carotid artery occlusion after other techniques had failed. A 68-year-old woman presented with an acute left internal carotid artery occlusion 4 days after mechanical thrombectomy of a left middle cerebral artery occlusion. She was not a candidate for intravenous thrombolysis because of a recent cerebral infarction. Attempts at mechanical thrombectomy using a stent retriever, contact aspiration, or combined contact aspiration and stent retriever were unsuccessful. The parallel stent retriever technique using two 6 × 25-mm Trevo stent retrievers enabled coverage of the entire thrombus, and successful reperfusion was achieved (extended Thrombolysis in Cerebral Infarction grade 2b). After the procedure, the patient was able to walk without assistance. Her modified Rankin Scale score was 2 at 90 days follow-up. Microscopic examination of the retrieved thrombi demonstrated red blood cells, fibrin, and partial endothelialization. The parallel Trevo stent retriever technique has the potential as rescue therapy for refractory large-vessel occlusion. However, complications arising from this technique remain uncertain. Further studies are needed to determine the effect of this technique in terms of recanalization and clinical safety.